Production And Characterisation Of Low Sodium Hydrolysates From Defatted Soy Flour [Glycine Max (L.) Merr.] And Roselle Seed Flour (Hibiscus Sabdariffa L.) - Wong, Kam Huei (2003)
The study investigated production and characterisation of low sodium hydrolysates from defatted soy flour (DSF) and roselle seed flour (RSF). The problem of high sodium content in acid hydrolysis was over-come by replacing partly sodium with other cations in the neutralisation process and using enzymatic hydrolysis method. The results showed that acid hydrolysates, neutralised with 75.0% sodium hydroxide, 12. 5% calcium hydroxide, and 12.5% potassium hydroxide, were at an acceptable level. The enzymatic hydrolysis of DSF and RSF by three different commercial enzymes- crude Bromelain, Flavourzyme and Protamex were studied. The enzyme decay experiment showed that all enzymes were inactivated at 100°C. They had both endopeptidase and exopeptidase activities, with Flavourzyme showing the most prominent exopeptidase properties. The pKa value for Bromelain with DSF (DB) was 7.39, while the optimum conditions were pH 6.5 at 55°C with 100 mg/ml enzyme at 3% protein substrate concentration.The pKa value for Flavourzyme with (DF) was 6.50, while the optimum conditions were pH 6.5, 50°C, with 200 mg/ml enzyme at 3% protein substrate concentration. For Protamex with DSF (DP), the pKa was 7. 50, while the optimum conditions were pH 6.5, 60°C, with 150 mg/ml enzyme at 3% protein substrate concentration. RSF with Bromelain (RB) had a pKa value of 6.97, optimum conditions were pH 7.0, 55°C, with 100 mg/ml enzyme at 2.5% protein substrate concentration. Flavourzyme with RSF (RF) had a pKa value of 6.80 and optimum activity was at pH 6. 5, 50°C, with 100 mg/ml enzyme at 3% protein substrate concentration. Protamex with RSF (RP) showed a pKa of 6. 49, while optimum conditions were at pH 5.5, 55°C, with 100 mg/ml enzyme at 3. 5% protein substrate concentration. DB had the highest degree of hydrolysis (DH) whereas RF had the lowest DH among the hydrolysates. After 5-hour hydrolysis, DP and RF produced a small peptide of about 90 Dalton (Da), similar in size to alanine. Amino acids released were determined by reverse phase chromatography and were used to predict the possible flavour properties of the hydrolysates obtained by comparing the flavour notes of amino acids that had undergone Maillard reaction. Most of the produced hydrolysates contained high amount of cysteine and glutamic acid. Therefore they were evaluated for meaty flavour and umami taste through sensory evaluation. Sensory evaluation studies showed that OF and RF have good potential as flavour ingredients or enhancers.